Seismic performance of Portuguese masonry infill walls: From traditional systems to new solutions - Silva, Luis M. (2019)
The use of masonry infill walls in reinforced concrete structures are a common solution in Portugal and other European countries for more than 50 years. These walls are used as exterior enclosures to build the envelope of the buildings, or as interior partitions to divide the different spaces of the houses. In the building construction practice these walls are built only after the hardening of the reinforced concrete elements. For that reason, they are assumed as non-structural elements, and not considered in the structural design of the building. However, when buildings are subjected to seismic action, these walls assume a structural behavior. This leads in many cases to the existence of an unsatisfactory behavior of infill walls, resulting in damage of the walls, which put human lives in dangerous and cause extensive economic losses. This seismic vulnerability of masonry infill walls is well recognized by the scientific community and has been observed in many works carried out in the last decades, as well as the recent earthquakes in southern Europe. In the case of a seismic event of high intensity in Portugal, it is expected that similar problems will occur in the Portuguese masonry infill walls, given the similarity of the construction typologies, in southern Europe. It is therefore important to study the masonry infill walls used in Portugal over the years, to fully understand their seismic behavior, and thus be able to propose and study reinforcement systems for existing walls and new masonry infill systems for new construction. Thus, in this paper is made a characterization of masonry infill walls typologies used in Portugal over the years. A review of the mechanical behavior of masonry infill walls is carried out using several In-Plane and Out-of-Plane tests performed at the University of Minho and other studies carried out in Portugal. Several strengthening techniques possible to be used in this type of walls are presented, as well as some mechanical characterization tests of these strengthening solutions applied on Portuguese infills walls. Finally, are presented two proposals for new systems of masonry infill walls to be used in new construction, with the objective of present a better seismic behavior in this type of elements